Journalistic Coverage of Organized Crime in Mexico: Reporting on the Facts, Security Protocols, and Recurrent Subthemes - Díaz Cerveró, Elba; Barredo Ibáñez, Daniel (International Journal of Communication, 2020)
Mexico is among the most violent countries for journalism, with more than 100 journalists killed in the past two decades. Behind these murders, which have largely gone unpunished, are phenomena such as organized crime and corruption, as well as a lack of state presence in some regions. In this study, we focus on analysis of a relevant topic in the contemporary news agenda, namely journalistic coverage of organized crime. For this, we interviewed almost two dozen Mexican journalists who work in Mexico’s main media outlets. Through journalists’ responses, we observe the normalization of violence in their everyday work. Although the journalists interviewed recognize that they do not have, in general, specific knowledge of this type of coverage, their experience directs them to develop security protocols, including use of their media outlets’ physical infrastructure and strategic use of social networks and the Internet.
Keywords: Crimen organizado - En la prensa - México; Mexico; Organized crime; Journalism studies; Drug trafficking; Journalists